Dakwah Subuh dan Filantropi Islam: Praktik Terbaik Pembelajaran Dakwah di Era Millenial - Suhirman Suhirman; Rini Fitria; Fathan Awwalur Rayyan (Institut Agama Islam Negeri Bengkulu, 2020)
Da'wah in the millennial era encountered many extraordinary obstacles. The presence of new media; the internet is believed to be the main driving factor that makes the mosque deserted from lecture activities. Pilgrims prefer to listen to lectures via mobile phones because they find popular clerics. Dawn preaching as a da'i and mad'u activity with face to face (face to face communication) is certainly very effective in getting inner enlightenment for mad'u, with the question and answer method will be efficient and effective messages that are conveyed in the morning breakfast interspersed . This study presents a best practice that collaborates lecture method with philanthropic goodness. Qualitative studies are selected through interviews and in-depth observation mechanisms. Al-Mubarakah Mosque in Bengkulu City was the location of the study. We found that Islamic philanthropy through serving breakfast after dawn propaganda was considered effective. Breakfast is provided from the mosque's cash fund from alms and infaq dawn worshipers. There is consistency in the presence of pilgrims, and even tends to increase even though it is not volatile. Ustadz provided material in accordance with the needs of pilgrims and the times.